Deciphering the rhizosphere bacteriome associated with biological control of tobacco black shank disease - Ma, Yi-Nan; Gu, Yi-Lin; Liu, Jing; Zhang, Yuqin; Wang, Xinwei; Xia, Zhenyuan; Wei, Hai-Lei (Frontiers in Plant Science, 2023)
Introduction The black shank disease seriously affects the health of tobacco plants. Conventional control methods have limitations in terms of effectiveness or economic aspects and cause public health concerns. Thus, biological control methods have come into the field, and microorganisms play a key role in suppressing tobacco black shank disease. Methods In this study, we examined the impact of soil microbial community on black shank disease basing on the structural difference of bacterial communities in rhizosphere soils. We used Illumina sequencing to compare the bacterial community diversity and structure in different rhizosphere soil samples in terms of healthy tobacco, tobacco showing typical black shank symptoms, and tobacco treated with the biocontrol agent, Bacillus velezensis S719. Results We found that Alphaproteobacteria in the biocontrol group, accounted for 27.2% of the ASVs, was the most abundant bacterial class among three groups. Heatmap and LEfSe analyses were done to determine the distinct bacterial genera in the three sample groups. For the healthy group, Pseudomonas was the most significant genus; for the diseased group, Stenotrophomonas exhibited the strongest enrichment trend, and Sphingomonas showed the highest linear discriminant analysis score, and was even more abundant than Bacillus; for the biocontrol group, Bacillus, and Gemmatimonas were the largely distributed genus. In addition, co-occurrence network analysis confirmed the abundance of taxa, and detected a recovery trend in the network topological parameters of the biocontrol group. Further functional prediction also provided a possible explanation for the bacterial community changes with related KEGG annotation terms. Discussion These findings will improve our knowledge of plant-microbe interactions and the application of biocontrol agents to improve plant fitness, and may contribute to the selection of biocontrol strains.